Research on the Glass Silicon Anodic Direct Bonding Parameters - Jia Li; Guo Hao; Guo Zhiping; Miao Shujing (Institute of Advanced Engineering and Science, 2015)
By MEMS packaging test platform for bonding process of bonding temperature and bonding time,and test silicon specifications experimental study.Firstly,according to the anodic bonding principle,the main factors to detemine the effect of bonding quality.Secodly,change the bonding temperature,bonding time,and test wafer size and other parameters,glass silicon bonding contrast test.Finally,the calculation and analysis of comparative test of each group is bonded porosity,summanrized the factors that affect the quality of the bonding and bonding to achieve the best results in the bonding conditions.Experimental results indicate that when the bonding voltage of 1200V,bonding temperature of 445-455c,bonding time is 60s,the void fractin is less than 5%.Glass and Silicon wafer bonding quality can achieve the best. The experimental results in order to improve the glass silicon bonding quaity provides the basis.